Fiscal Responsibility and Reform of the Brazilian State (1998-2000) (Tempo e Argumento, 2024)
In times of economic crisis and an ever-increasing reduction in the State's role in the direct execution of public policies, under the allegation that it no longer has the financial conditions to bear the social debt owed to its citizens, a weakening of constitutional protections aimed at achieving material justice among citizens and the deficit in the provision of public services. Alongside the budgetary problems and the implementation of social rights, the misappropriation of funds and the private appropriation of public assets are denounced, which have long been noted in Brazilian historiography. This way of conducting the res publica harms everyone, as it makes the taxpayer bear the consequences of poor management and application of public resources, whether through increased taxes, reduced investments, or cuts in programs. social. Considering this problem and with deductive method and legislation and bibliography research, from the period between 1998 and 2001 in Brazil, the paper analysis of the most recent Brazilian Administrative Reform, principle of efficiency and Administration Public managerialism. Finally, it will analyze Complementary Law 101/2000 (Fiscal Responsibility Law) and the changes it brought to the implementation of managerial and participatory administration.
Keywords: Fiscal Responsibility Law; Management Reform; Principle of Transparency; Principle of Efficiency; Social Control